Impact of Communication on Employees during Organizational Transformation - Hyder, Mohammed Sayeeduddin (Global journal of Business and Integral Security, 2023)
Organizational transformation is a process that involves significant changes in an organization’s structure, processes, and systems. Such transformations are often initiated to improve the organization’s performance, enhance its competitiveness, and adapt to changing business environments. However, implementing organizational transformations can be challenging and can lead to stress, anxiety, and uncertainty among employees. Effective communication is crucial during this process to alleviate employee concerns, maintain their motivation and engagement, and facilitate a smooth transition. The impact of communication on employees during organizational transformation is a critical area of research. The study aims to examine the effects of communication on employees during organizational transformation and how it influences their attitudes and behavior. The study also explores the role of different communication channels, such as face-to-face meetings, emails, and intranet portals, in shaping employees’ perceptions and responses. The study found that effective communication plays a crucial role in mitigating employees’ negative reactions to organizational transformation. Employees who received timely and clear information about the changes were more likely to feel informed, engaged, and motivated. Communication helped employees understand the reasons for the transformation, the expected outcomes, and their role in the process. As a result, employees felt more in control of their situation, which reduced their anxiety and stress levels. The study also found that different communication channels had varying effects on employees’ perceptions and responses. Face-to-face communication was found to be the most effective channel, as it allowed for two-way communication and personalized interaction between employees and their leaders. Emails and intranet portals were found to be less effective, as they were often generic and lacked the personal touch that face-to-face communication provided. The study also found that the style of communication and the Leadership behavior during organizational transformation also had a major impact on employees. Moreover, the study found that communication should be a continuous process, and not just limited to the initial stages of organizational transformation. Ongoing communication helped employees stay informed and engaged, which reduced the likelihood of resistance and increased their commitment to the transformation process. Regular communication also helped identify and address any issues or concerns that employees may have had, which prevented the escalation of problems.